A comparative study of diagnostic performance of COVID-19 Reporting and Data System and computed tomography severity score in clinically suspected COVID-19 patients - Vikram Kyatham; Yarramsetty Pundari Kashudu; T.R. Nagendra; Rama Rao Piprikar; Rhidaynath A Kogekar; Rahul Bhargava (The Journal of Association of Chest Physicians)
Purpose: The aim of this study was to compare the diagnostic performance of COVID-19 Reporting and Data System (CO-RADS) and computed tomography (CT) severity score (CT-SS) in patients with clinically suspected coronavirus disease. Methods: A cross-sectional study was done. Patients presenting to the emergency department with symptoms suspicious for COVID-19 were participated. Patients referred with a positive reverse transcription polymerase chain reaction (RT-PCR) had chest CT evaluation done by CO-RADS and CT-SS, respectively, by an independent investigator. A binomial logistic regression analysis was performed to calculate the sensitivity, specificity, diagnostic accuracy, positive predictive value (PPV), and negative predictive value (NPV) of the two scoring systems in diagnosing COVID infection, considering RT-PCR as the reference standard. Results: A total of 400 cases were evaluated. Two hundred sixty-eight patients with a clinical suspicion of COVID-19 had a positive RT-PCR. The mean duration of symptoms was 5.5 ± 3.4 (range, 1–21 days). The mean CO-RADS and CT-SS scores were 3.7 ± 1.4 (range, 1–5) and 9.1 ± 7.5 (range, 0–28), respectively. Air leaks, including pneumothorax, pneumomediastinum, and surgical emphysema, were observed in six cases. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of CO-RADS was 93.8, 80, 90.7, 92.1, and 90%, respectively. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of CT-SS were 95, 76, 86, 89, and 85%, respectively. The area under the curve (AUC) for CO-RADS was 0.943 [95% confidence interval (CI), 0.909–0.976, P < 0.001] and AUC for CT-SS was 0.877 (95% CI, 0.821–0.933, P < 0.001), respectively. The cut-off values of CT-SS and CO-RADS were 7.1 and 4.2, respectively. Conclusion: Both scoring systems had good sensitivity, specificity, and diagnostic accuracy in comparison to RT-PCR test to diagnose COVID-19 infection.